Penjaminan Mutu Pendidikan di Raudhatul Athfal - Siti Muyasaroh (Tarbiyah Departement collaboration with AMCA, 2017)
Quality assurance is how to organize all the activities and educational resources aimed at customer satisfaction in Raudhatul Athfal. Everyone involved in the educational process of carrying out the task with vigor and participate in the improvement of educational services so as to provide educational services that meet or exceed customer expectations. Implementation of quality assurance systems in Raudhatul Athfal run PDCA system, which is oriented to meet the quality standards that have been defined and are internal. Implementation PDCA will impact on the emergence of Kaizen in the Raudhatul Athfal.